A PROSPECTIVE OBSERVATIONAL STUDY OF CORTICOSTEROIDS USED IN A TERTIARY CARE CORPORATE HOSPITAL - M. Praveen Kumar; K. Bhanu Prasad; Aziza Tahaseen; K. Rahul; M. Sree Lakshmi; V. Kalyan Chakravarthy (Medico Research Chronicles, 2018)
Objectives: Evaluation of a prospective observational study of the corticosteroids used in tertiary care hospital , to provide information and correct rationale pertaining to corticosteroids which also describes various interactions and adverse effects of corticosteroids to assess the statistical incidence regarding usage and its right provision. Methodology: Study site was at SUNSHINE HOSPITALS, conducted for a period of 6 months. Both male and female individuals of age group 16-75years were included. Results: Study included assessment of interactions, adverse effects and the rational usage of corticosteroids with total of 200 prescriptions; of which 34 pharmacokinetic drug interactions, 71 pharmacodynamic drug interactions and 9 major adverse effects were observed. The rational usage of drug was assessed based on proper indication, drug selection, goal and administration. Conclusion: To conclude with, corticosteroids are effective drugs in an array of treatment of diseases involving careful consideration of factors such as potency, formulation, responsiveness and cost. Measures for prevention and early recognition of drug induced effects are important for better patient outcome.